Quality maintenance of ‘Laetitia’ plum by application of 1- methylcyclopropene, ethanol vapor and heat treatment - De Martin, Mariuccia Schlichting; Steffens, Cristiano André; Pavarin, Diego Fernando; Rodrigues, Marília Farias; Amarante, Cassandro Vidal Talamine do; Brackmann, Auri (Comunicata Scientiae, 2018)
The aim of this study was to evaluate the effect of 1-methylcyclopropene (1-MCP), ethanol and heat treatment on ripening behavior and internal browning occurrence of ‘Laetitia’ plum stored under regular air. The treatments were: control, 1-MCP (1,0 µL L-1), ethanol (500 and 1500 µL L-1) and heat treatment (37 and 40 °C) for 24 h. Fruit were stored under regular air for 25 or 35 d at 0.5±0,1 °C and 96±1% relative humidity (RH), and assessed for respiration rate, ethylene production, skin color, flesh firmness, titratable acidity, soluble solids content, incidence of decay and incidence and severity of internal flesh browning. In both storage periods, immediately at removal from cold room, fruit from all the treatments showed lower respiration rate and ethylene production than control fruit. Ethanol vapor at 1500 µL L-1, 1-MCP at 1,0 µL L-1 and heat treatment at 40 °C allowed a less reddish skin after 35 d of storage, as well as higher flesh firmness and lower intensity of internal flesh browning than control fruit, in both evaluated storage periods. In either 25 or 35 d of storage period, heat treatment at 40 °C increased the occurrence of decay. All the treatments provided lower incidence of internal flesh browning than control fruit in both evaluations. The postharvest application of ethanol at 1500 µL L-1, 1-MCP at 1,0 µL L-1 and heat treatment at 40 °C for 24 h delay the ripening process and reduce the incidence of internal flesh browning of ‘Laetitia’ plum.